Замонавий криптографик алгоритмлар учун катта туб сонларни генерациялаш масалалари - Норматов, Ш.Б (ILIM hám JÁMIYET, 2016)
This article analyzed the role of large prime numbers in modern cryptography; calculate the number of prime numbers in this range, the methods of verification of the simplicity and the principle of the use of a table of prime numbers.